PENGEMBANGAN MODUL BERBASIS PROBLEM BASED LEARNING PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS V - Hendriani, Maifit; Efna Deza, Cynthia (Jurnal Riset Pendidikan Dasar Dan Karakter, 2024)
This research is based on problems identified in Grade V at MIN 5 Pesisir Selatan, where the learning modules used were less engaging and did not implement any specific learning model. In addition, teachers' limited ability to design and develop modules has led to low module usage among students. This study aims to develop a Problem-Based Learning (PBL)-based module for integrated thematic learning. The development model used is the 4-D model, which consists of the stages: define, design, develop, and disseminate. Data collection techniques involved validation sheets assessed by experts in content, language, and design. The validation results indicate that the developed PBL-based module is valid. This is supported by validation scores from content experts of 91.9% and 96.4% (very valid), from the language expert 86.1% (valid), and from the design expert 88.46% (valid).